Mucilaginibacter hurinus sp. nov., isolated from briquette warehouse soil - Choi, Lina; Zhao, Xinran; Song, Yali; Wu, Minghan; Wang, Gejiao; Li, Mingshun (Archives of microbiology, 2020)
A novel bacterial strain, designated ZR32 T , was isolated from briquette warehouse soil in Ulsan (Korea). The strain was aerobic, showing pink-colored colonies on R2A agar. Phylogenetic analyses based on 16S rRNA gene sequences showed that strain ZR32 T was closely related to Mucilaginibacter soli R9-65 T (97.0%), Mucilaginibacter gynuensis YC7003 T (96.9%), and Mucilaginibacter lutimaris BR-3 T (96.8%). The values of DNA–DNA relatedness related two highest strains M. soli R9-65 T and M. gynuensis YC7003 T were 31.2 ± 6.9% and 19.7 ± 0.3%, respectively. Its genome size was 3.9 Mb, comprising 3402 predicted genes. The DNA G+C content of strain ZR32 T was 43.0 mol%. The major cellular fatty acids (> 5% of total) were summed feature 3 (C 16:1 ω 6 c and/or C 16:1 ω 7 c ), C 16:0 , C 16:1 ω 5 c , iso-C 15:0 , iso-C 17:0 3-OH, and C 17:1 ω 9 c . The major respiratory quinine was menaquinone-7 (MK-7). The major polar lipids were phosphatidylethanolamine, two unidentified phospholipids, one unidentified sphingolipid, and one unidentified polar lipid. Strain ZR32 T showed distinctive characteristics such as the temperature and pH for growth ranges, being positive for β-glucosidase, salicin production, negative for N -acetyl-glucosamine assimilation, being resistant to carbenicillin and piperacillin to related species. On the basis of phenotypic, chemotaxonomic, and phylogenetic data, strain ZR32 T represents a novel species of the genus Mucilaginibacter , for which the name Mucilaginibacter hurinus sp. nov. is proposed. The type strain is ZR32 T (= KCTC 62193 = CCTCC AB 2017285).